Pros and Cons Controversy on Synchrotronic Biosensor Using Os–Pd/HfC Nanocomposite for Tracking, Monitoring, Imaging, Measuring, Diagnosing and Detecting Cancer Cells, Tissues and Tumors - Heidari, Alireza (Indonesian Journal of Cancer Chemoprevention, 2021)
In the current paper, optimization of Tri Propyl Amine (TPrA) concentrations and Os–Pd/HfC nanocomposite as two main and effective materials in the intensity of synchrotron for tracking, monitoring, imaging, measuring, diagnosing and detecting cancer cells are considered so that the highest sensitivity obtains. In this regard, various concentrations of two materials were prepared and photon emission was investigated in the absence of cancer cells.Keywords: Synchrotronic Biosensor, Os–Pd/HfC Nanocomposite, Photomultiplier, Hafnium(IV) Carbide (HfC) Nanoparticles, Tracking, Monitoring, Imaging, Measuring, Diagnosing, Detecting, Cancer Cells, Osmium bis(2,2'–bipyridine)chloride.